Validity, reliability, and invariance across sex of a German version of the Behavioral Regulation in Exercise Questionnaire - Cocca, Armando; Kopp, Martin; Greier, Klaus; Labek, Karin; Cocca, Michaela; Ruedl, Gerhard (Frontiers in Psychology, 2024)
Objective. Since there is no scientifically validated German version of the Behavioral Regulation in Exercise Questionnaire (BREQ-3), the aim of this study is to assess its psychometric parameters and invariance across sex in a sample of German-speaking young adults. The BREQ-3 is an instrument measuring the social and internal influences of motivation towards exercising. This tool is widespread within the scientific community and has been validated in several languages. Methods. A total of 271 participants (45% women; mean age = 20.67 ± 2.17 years; effect size ≥ 0.5) filled in the BREQ-3 at one time point, with a small sub-sample (n = 37) responding it a second time after 15 days. Confirmatory Factorial Analysis, Structural Modelling, and Intraclass Correlation Coefficient were used to examine the German version of the questionnaire. Results. Results highlighted a good fit of the six-dimensional model after the removal of two items (CFI = .912; SRMR = .0594; RMSEA = .064), as well as full invariance across sex (pχ2 = .218; ΔCFI < .01). Internal consistency and reliability were moderate to good. Conclusions. The 22-item German BREQ-3 is a scientifically valid instrument that can be used in cross-national studies dealing with social aspects of exercise behaviors.